Hyperglycemia in Severe Falciparum Malaria: A Case Report - Leonardo Chianura; Isabella Corinna Errante; Giovanna Travi; Roberto Rossotti; Massimo Puoti (Case Reports in Critical Care)
Occasionally, malaria may present with unusual signs and symptoms. We report a case of an uncommon presentation of Plasmodium falciparum infection in a 59-year-old Ethiopian immigrant, which initially presented with hyperglycaemia and multiple organ dysfunction syndrome (MODS). Reports of unusual presentations of malaria are few and cases of severe malaria with hyperglycaemia are rarely described. As hyperglycaemia is associated to most severe malaria and high mortality, our aim is to catch the attention of the physicians on this entity.